The identity of Clematis dongchuanensis (Ranunculaceae) from northeastern Yunnan, China - Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2020)
We demonstrate that Clematis dongchuanensis (Ranunculaceae), described from Dongchuan in northeastern Yunnan, China and considered to be related to C. repens in having simple leaves, erect sepals and pubescent filaments and anthers, is identical with C. connata var. trullifera, a taxon with pinnate leaves of 5−7 (9) leaflets. The simple leaves described in C. dongchuanensis are actually leaflets of a pinnate leaf in C. connata var. trullifera. We therefore place C. dongchuanensis in synonymy with C. connata var. trullifera. Lectotypification is proposed for C. connata var. trullifera and for C. coriigera, a synonym of C. connata var. trullifera.